2011
DOI: 10.1086/657925
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Driven Regime Shifts in the Dynamics of Size-Structured Populations

Abstract: Global warming impacts virtually all biota and ecosystems. Many of these impacts are mediated through direct effects of temperature on individual vital rates. Yet how this translates from the individual to the population level is still poorly understood, hampering the assessment of global warming impacts on population structure and dynamics. Here, we study the effects of temperature on intraspecific competition and cannibalism and the population dynamical consequences in a size-structured fish population. We u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
118
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 84 publications
(121 citation statements)
references
References 48 publications
3
118
0
Order By: Relevance
“…In our model we also assume asymmetric competition between life stages. This assumption is supported by physiological observations and modeling results suggesting that smaller-sized perch tend to be more efficient than larger ones in exploiting a common resource (Persson and De Roos 2006, Ohlberger et al 2011a showed that populations are likely to be reproduction limited when juveniles are superior to adults with respect to resource competition (or have lower mortality) and that in such systems increases in mortality induce a compensatory effect in the juvenile stage. The extent of the compensatory response depends on the degree to which mortality rate increases, because juvenile biomass changes with adult mortality according to a hump-shaped relationship , Schro¨der et al 2009).…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…In our model we also assume asymmetric competition between life stages. This assumption is supported by physiological observations and modeling results suggesting that smaller-sized perch tend to be more efficient than larger ones in exploiting a common resource (Persson and De Roos 2006, Ohlberger et al 2011a showed that populations are likely to be reproduction limited when juveniles are superior to adults with respect to resource competition (or have lower mortality) and that in such systems increases in mortality induce a compensatory effect in the juvenile stage. The extent of the compensatory response depends on the degree to which mortality rate increases, because juvenile biomass changes with adult mortality according to a hump-shaped relationship , Schro¨der et al 2009).…”
Section: Discussionmentioning
confidence: 72%
“…First, we do not consider evolutionary change in lifehistory traits, such as changes in size at maturity. Indeed, length at maturity in perch has previously been shown to have slowly increased before but rapidly decreased after the pathogen outbreak, which may have contributed to a shift in reproduction rate (Ohlberger et al 2011a). Although the smaller size at maturation increased the proportion of mature 2-year-old fish, this effect can be assumed to be negligible for the biomass analyses, because the increase was only a few percent (Ohlberger et al 2011a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Continuous structure due to body size has been studied using detailed physiologically structured population models (Metz and Diekmann 1986), but the method has been applied to only very few wild populations (e.g., Ohlberger et al 2011a). Physiologically structured population models have a continuous timescale and a high level of complexity, and the data requirements are therefore difficult to meet for many wild study populations.…”
Section: Introductionmentioning
confidence: 99%
“…However, fish are poikilotherms and are therefore sensitive to changes in thermal conditions of their environment. Temperature has a direct effect on fish activity, growth, metabolism, reproduction and development but can also influence communities and populations via biotic interactions (Petchey et al, 1999;Voigt et al, 2003;O'Connor et al, 2009;Rall et al, 2010;Yvon-Durocher et al, 2010;Ohlberger et al, 2011;Vucic-Pestic et al, 2011;Reuman et al, 2014). From this viewpoint, 1-3°C increase in temperature due to global warming have been shown to have major impacts on fish community structure and diversity (Daufresne et al, 2004(Daufresne et al, , 2009Daufresne and Boet, 2007).…”
Section: Water Temperaturementioning
confidence: 99%